POLYCYSTIC OVARIAN SYNDROME UNVEILED: NAVIGATING THE COMPLEXITIES AND IMPACTS ON WOMEN’S REPRODUCTIVE HEALTH - Muhammad Ibtisam Elahi; Akif Saeed; Maryam Bakhat; Laiba Zahid; Ayesha Mansoor; Munaza Sabir; Muhammad Mudassar; Amna Bashir; Ayesha Bintay Farooq; Muhammad Akram; Aiman Aziz; Momina Iftikhar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
PCOS, also known as polycystic ovarian syndrome, disturbs 6% to 15% of females of reproductive age. Many clinicians find it difficult to identify this widespread condition due to the lack of clear diagnostic criteria. Additionally, a patient may present to any number of clinicians due to the disorder's numerous presentations, including internists, family practitioners, nurse practitioners, pediatricians, gynecologists, endocrinologists, or dermatologists. Moreover, a patient's most troubling PCOS symptom may vary over time from hirsutism as an adolescent to sterility as a young mature necessitating visits to multiple doctors along the way. Therefore, it is critical that healthcare providers comprehend not just the specialty-specific management concerns but also the additional health risks associated with these women. Insulin resistance has been found to play a significant role in the pathophysiology of PCOS, highlighting the long-term risks associated with diabetes mellitus and the resulting elevated risk of coronary artery disease. Inconsistent menstruation and hirsutism are no longer considered harmless annoyances. The diagnosis/differential diagnosis and treatment options, the two most perplexing aspects of polycystic ovary syndrome for the practicing provider, will be the main topics of this study. The significance of insulin resistance (IR) and the potential treatment benefit of insulin sensitizers are particularly emphasized. Additionally, the advantage and critical nature of lifestyle changes for these women's long-term health are highlighted. It is believed that more clarity in this area will enable more women to receive the appropriate diagnosis and treatment for their presenting symptoms (hirsutism, irregular menses, etc.) as well as to receive education and care for the long-term health risks of IR.